Comparison of Intra-lesional Methotrexate and Intra-lesional Triamcinolone Acteonid in the treatment of Localized Alopecia Areata - Saira Rafique, Tahir Hassan, Muhammad Khurram Shahzad, Naima Aliya, Sumaira Rafique, Sarwar Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the common reasons of non-scarring, patchy or confluent hair loss that can affect any part of the body, but most frequently the scalp, is alopecia areata. Alopecia areata (AA) has a variety of therapy options, but it is still a difficult condition with varied severity, recurrence, and a significant cosmetic problem. Aim: To compare the effects of intralesional triamcinolone acetate and intralesional metatrexate in the treatment of localized alopecia areata in patients at the dermatology department. Study design: Comparative clinical study. Methodology: The dermatology division of Sheikh Zayed Hospital Rahim Yar Khan conducted the current study. The current study included 128 participants. Each chosen group included 64 patients. The sample size was calculated assuming a research power of 80%, a confidence level of 95%, and an efficacy of 60.0% for methotrexate and 80.0% for triamcinolone. Using a 30-gauge needle connected to an insulin syringe, both groups will get intralesional injections in patches with alopecia areata three weeks apart for a maximum of four sessions. A follow-up will be conducted a year following the end of the treatment. The analysis of the data was done using SPSS 23. Chi-square/exact Fisher's tests were performed to examine the gender distribution, results, respondents, and recurrence rate between the two groups with a p-value of less than 0.05. Results: Patients in group A had an average age of 29.2 +/-3.8 years, whereas those in group B had an average age of 30.0 +/-2.1 years. There was no discernible difference in the mean age of the patients between the two groups, according to an independent sample t test (p = 0.178). The gender distribution between the two groups is not significantly different, according to the p-value of 0.857. The p-value of 0.115 shows that there was no discernible difference in the two groups' rates of remission. The p-value of 0.188 shows that the two groups' recurrence rates did not differ significantly from one another. Practical Implication: This study helped researchers investigate the efficacy of intra-lesional triamcinolone acetonide as a treatment for localized alopecia areata due to its accessibility and safety. Second, it added to the corpus of information in the field regarding alternative, successful treatment options that are comparable. Conclusion: It was determined that there was no statistically significant difference between the outcomes for the Triamcinolone group and the Methotrexate group. Keywords: Alopecia Areata, Efficacy, Intralesional Methotrexate, Triamcinolone Acetonide and Clinical Outcomes.